2012
DOI: 10.2174/1876525401204010014
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Freezing on the Mechanical Properties of Bone

Abstract: Abstract:The serious health risks posed by bone fractures create a growing need for accurately diagnosing fracture risk. The Reference Point Indentation instrument (RPI) directly measures key mechanical properties in vivo to assess bone fracturability. There is a wealth of information that could be obtained from measuring cryopreserved bone samples with the RPI. Since it is unknown how freezing affects these key mechanical properties, measuring a cryopreserved sample gives no indication of the sample's origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 19 publications
1
16
0
2
Order By: Relevance
“…Fourth, the presence of the fracture also limited indentation, necessitating a testing location likely to reduce the RPI depth in this group: ie, more distal (negative correlation, r = –0.31 to –0.38, p < 0.05) and missing superolateral measurements associated with higher indentation depth in 40% of samples. Finally, freezing has previously been shown to have minimal effect on bone properties such as stiffness or strength or RPI, which also applies to this study ( r = –0.11 to 0.12 and p > 0.05). Additionally, in this study, the fracture samples were carefully stored (shorter period before freezing, shorter storage duration, lower temperature and better hydrated).…”
Section: Discussionsupporting
confidence: 76%
“…Fourth, the presence of the fracture also limited indentation, necessitating a testing location likely to reduce the RPI depth in this group: ie, more distal (negative correlation, r = –0.31 to –0.38, p < 0.05) and missing superolateral measurements associated with higher indentation depth in 40% of samples. Finally, freezing has previously been shown to have minimal effect on bone properties such as stiffness or strength or RPI, which also applies to this study ( r = –0.11 to 0.12 and p > 0.05). Additionally, in this study, the fracture samples were carefully stored (shorter period before freezing, shorter storage duration, lower temperature and better hydrated).…”
Section: Discussionsupporting
confidence: 76%
“…When evaluating the effects of freeze-thaw cycles in bone, the effects were found to vary depending on the type of bone assessed, but in most cases were not measureable. If degradation did occur, the effect of freezing on the mechanical properties was smaller than the natural variation of those properties across a sample before freezing (24). A similar study of dental pulp showed that storage in transportation solution for 24 h had no significant negative effects on the histological or mechanical properties of the pulp tissue extracted from the cryopreserved intact teeth (25).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms were postulated to this effect, that is, either by freezing expansion of the water or by damage to the collagenous matrix. Experimental data range from “no effect” [ 15 ] to “slight damage” (maximum 15%) [ 16 ]. In a recent study, the freezing of rat tibiae was found to have no effect on the bone-implant interface [ 17 ].…”
Section: Discussionmentioning
confidence: 99%